"Counting votes" in public responses to scientific disputes. (July 2018) - Johnson, Branden B.
Publicized disputes between groups of scientists may force lay choices about groups' credibility. One possible, little studied, credibility cue is vote-counting (proportions of scientists on either side): for example, "97%" of climate scientists believe in anthropogenic climate change. An online sample of 2600 Americans read a mock article about a scientific dispute, in a 13 (proportions: 100%–0%, 99%–1%, … 50%–50%, … 1%–99%, 0%–100% for Positions A and B, respectively) × 8 (scenarios: for example, dietary salt, dark matter) between-person experiment. Respondents reported reactions to the dispute, attitudes toward the topic, and views on science. Proportional information indirectly affected judged agreement but less so topic or science responses, controlling for scenarios and moderators, whether by actual proportions or differing contrasts of "consensus" versus "near-consensus." Given little empirical research with conflicting findings, even these low effect sizes warrant further research on how vote-counting might help laypeople deal with scientific disputes.